Pengaruh Perpustakaan Digital Dalam Meningkatkan Minat Membaca - Karim, Abdul; S, M Rizki; Rahma, Tarisa; Sari, Sovie Novita (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
The purpose of this article is to provide a deeper explanation of the benefits of digital libraries in increasing the reading interest of the millennial generation in the era of globalization. The method used is a literature study in order to find out about digital libraries and the reading interest of the Indonesian people by utilizing library material sources to obtain research data. The low interest in reading for the Indonesian people has a negative impact on society, especially the rapid development of information technology and digitalization that has a considerable influence on society, especially for the millennial generation. Therefore, the presence of this digital library is expected to be put to good use in increasing the reading interest of the millennial generation more effectively and efficiently because they can directly access the digital library quickly. In the future, it is hoped that the millennial generation can take advantage of this digital library to increase their interest in reading. In order to compete with other countries and give birth to the next generation of the nation who are smart, competent, and qualified.